Cardiopulmonary Coupling Spectrogram as an Ambulatory Method for Assessing Sleep Disorders in Patients With Autoimmune Encephalitis - Liao, Jinchi; Lu, Yi; Lu, Yaxin; Huang, Yu; Wang, Yuge; Long, Ling; Hu, Xueqiang; Lu, Zhengqi; Qiu, Wei; Shu, Yaqing (Neurology, 2024)
Sleep disorders are a common and important clinical feature in patients with autoimmune encephalitis (AE); however, they are poorly understood. We aimed to evaluate whether cardiopulmonary coupling (CPC), an electrocardiogram-based portable sleep monitoring technology, can be used to assess sleep disorders in patients with AE. Patients fulfilling the diagnostic criteria of AE were age- and sex-matched with recruited healthy control subjects. All patients and subjects received CPC testing between August 2020 and December 2022. Demographic data, clinical information, and Pittsburgh Sleep Quality Index (PSQI) scores were collected from the medical records. Data analysis was performed using R language programming software. There were 60 patients with AE (age 26.0 [19.8-37.5] years, male 55%) and 66 healthy control subjects (age 30.0 [25.8-32.0] years, male 53%) included in this study. Compared with healthy subjects, patients with AE had higher PSQI scores (7.00 [6.00-8.00] vs 3.00 [2.00-4.00], < 0.001), lower sleep efficiency (SE 80% [71%-87%] vs 92% [84%-95%], < 0.001), lower percentage of high-frequency coupling (25% [14%-43%] vs 45% [38%-53%], < 0.001), higher percentage of REM sleep (19% ± 9% vs 15% ± 7%, < 0.001), higher percentage of wakefulness (W% 16% [11%-25%] vs 8% [5%-16%], = 0.074), higher low-frequency to high-frequency ratio (LF/HF 1.29 [0.82-2.40] vs 0.91 [0.67-1.29], = 0.001), and a higher CPC-derived respiratory disturbance index (9.78 [0.50-22.2] vs 2.95 [0.40-6.53], < 0.001). Follow-up evaluation of 14 patients showed a decrease in the PSQI score (8.00 [6.00-9.00] vs 6.00 [5.00-7.00], = 0.008), an increased SE (79% [69%-86%] vs 89% [76%-91%], = 0.030), and a decreased W% (20% [11%-30%] vs 11% [8%-24], = 0.035). Multiple linear regression indicated that SE (-7.49 [-9.77 to -5.21], < 0.001) and LF/HF ratio (0.37 [0.13-0.6], = 0.004) were independent factors affecting PSQI scores in patients with AE. Sleep disorders with autonomic dysfunction are common in patients with AE. Improvements in the PSQI score and SE precede the restoration of sleep microstructural disruption in the remission stage. CPC parameters may be useful in predicting sleep disorders in patients with AE.